Hydrogels: Assembly of Viral Hydrogels for Three‐Dimensional Conducting Nanocomposites (Adv. Mater. 30/2014). (August 2014) - Chen, Po‐Yen; Hyder, Md Nasim; Mackanic, David; Courchesne, Noémie‐Manuelle Dorval; Qi, Jifa; Klug, Matthew T.; Belcher, Angela M.; Hammond, Paula T.
<x xml:space="preserve">Abstract</x> The cover image represents a bioengineered M13 virus (grey) that can be genetically programmed to bind pristine singlewalled nanotubes (SWNTs) (black) in a controlled fashion along the length of the virus homo geneously. These SWNTs–virus complexes are used as the basis for the formation of crosslinked hydrogel scaffolds for the design of 3D porous polyaniline nanostructures (green) which integrate SWNTs, as reported by P. T. Hammond, A. M. Belcher, and co‐workers on page 5101. The templated assembly promises facile synthesis of 3D conducting nanocomposites for a myriad of applications, from sensing to energy conversion and energy storage. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>